Workshop Math And Science Untuk Menstimulus Kognitif PAUD Melalui Kegiatan Fun Cooking - Diah Harmawati; Nurlayli Hasanah (Universitas Negeri Makassar, 2019)
Goal of this Charity Program is giving experience and knowledge of teacher about Introducing Math and Science to stimulate The Cognitive Growing of students in Kindergarten by Fun Cooking activities making healthy, nutritious and interesting dish at Satu Atap (Satap) Wasur Kindergarten. This Charity Program will be conducted in 2 days at Satap Wasur Kindergarten of Merauke that involved all of the teachers as participant. Discussion and practice is the method to explain the activities of introducing math and science to the Kindergarten is important for the teachers during sharing and remembering their former knowledge appropriate with the up to date changes and development. It means that knowledge and concept of interesting introduce math and science fit with the growing step of the students in Kindergarten.